The check-up: in-person, computerized, and telephone adaptations of motivational enhancement treatment to elicit voluntary participation by the contemplator - Picciano Joseph F; Roffman Roger A; Walker Denise D; Stephens Robert S (BMC, 2007)
Abstract Countless barriers come between people who are struggling with substance abuse and those charged with providing substance abuse treatment. The check-up, a form of motivational enhancement therapy, is a harm reduction intervention that offers a manner of supporting individuals by lowering specific barriers to reaching those who are untreated. The check-up was originally developed to reach problem drinkers who were neither seeking treatment nor self-initiating change. The intervention, marketed as an opportunity to take stock of one's experiences, involves an assessment and personalized feedback delivered with a counseling style termed motivational interviewing. Check-ups can be offered in care settings to individuals who, as a result of screening, manifest risk factors for specific disorders such as alcoholism. They can also be free-standing and publicized widely to the general public. This paper will discuss illustrations of in-person, computerized, in-school, and telephone applications of the free-standing type of check-up with reference to alcohol consumers, adult and adolescent marijuana smokers, and gay/bisexual males at risk for sexual transmission of HIV. The paper's major focus is to highlight how unique features of each application have the potential of reducing barriers to reaching specific at-risk populations. Also considered are key policy issues such as how check-up services can be funded, which venues are appropriate for the delivery of check-up interventions, pertinent competency criteria in evaluating staff who deliver this intervention, how marketing can be designed to reach contemplators in untreated at-risk populations, and how a check-up's success ought to be defined.